Analysis Of The Implementation And Implications Of OECD/G20 Pillar One On The Taxation System In Indonesia - Fajar, Fadlol Muhammad; Irawan, Ferry (WIM Solusi Prima, 2024)
One of the efforts taken by member countries of OECD/G20 Inclusive Framework for BEPS is to capture tax revenue from the digital economy is called Pillar One: Unified Approach specifically Amount A. This research aims to obtain information on the progress and obstacles on the implementation of Pillar One in Indonesia, including the impact generated by Pillar One as well as understand policy alternatives that could potentially become replacement for Pillar One. The method used in this research is qualitative with a case study approach. The results obtained in this study show that currently Pillar One cannot be implemented because it encounters various obstacles and is related to other jurisdictions. If Pillar One has been implemented, the implications are additional tax revenue potential but relatively low, adjustment on policy, tax administration systems, IT systems and human resources. Pillar One, which has the potential to be canceled, raises alternative policies that can be implemented by Indonesia such as Digital service tax, Article 12B UN Model Convention and new PE criteria namely Significant Economic Presence. The government must reconsider the cost and benefit on implementation of Pillar One. The government must also prepare and compile alternative policies and supporting aspects such as IT system development due to the potential failure of the Pillar One implementation.